Diffusion and statistical analysis of STITCH-256 - Jamil N.; Mahmod R.; Z'aba M.R.; Udzir N.I.; Zukarnain Z.A. (2023)
Hash function is an important cryptographic primitive used in a wide range of applications, for example, for message authentication and in digital signatures. MD 4/5 and SHA-0/1/2 are examples of widely used hash functions, but except for SHA-2 (SHA-224, 256, 384, 512), they were all broken in 2005 after more than a decade of use. Since, then, the structure and components of cryptographic hash functions have been studied and revisited extensively by the cryptographic community. STITCH-256 was introduced to overcome problems faced by the MD- and SHA-family hash functions. STITCH-256 employs the Balanced Feistel network and its step operation runs in four parallel branches. The algorithm was claimed to produce good diffusion and its outputs were claimed to be random. To evaluate its suitability for such purposes, avalanche and empirical statisti- cal tests are commonly employed to show that there is empirical evidence supporting the claims. In this study, we report on the studies that were conducted on the 1000 sample of 256 bit of output from STITCH-256 algorithm. The studies include the study of diffusion and statistical properties of STITCH-256 using avalanche test and nine statistical tests. The results suggest that the claims were true where STITCH-256 produces good avalanche effect, thus good diffusion property and its outputs appear random. 2013 Asian Network for Scientific Information.